Using Black Holes Algorithm in Discrete Space by Nearest Integer Function - Mostafa Nemati; Navid Bazrkar; Reza Salimi; Behdad Moshref (IAES International Journal of Artificial Intelligence (IJ-AI), 2013)
In this paper we Using Black Holes Algorithm in Discrete Space by Nearest Integer Function. Black holes algorithm is a Swarm Algorithm inspired of Black Holes for Optimization Problems. We suppose each solution of problem as an integer black hole and after calculating the gravity and electrical forces use Nearest Integer Function. The experimental results on different benchmarks show that the performance of the proposed algorithm is better than    PSO (Binary Particle Swarms Optimization), and GA (Genetic Algorithm).DOI: http://dx.doi.org/10.11591/ij-ai.v2i4.4319